Integrated Study of CO2 Sequestration and CO2-EOR in Oil Reservoir by Compositional Simulation - Islam, Mohammad Amirul; Woobaidullah, ASM (Dhaka University Journal of Science, 2022)
Now researchers are performing extensive research work to increase the oil and gas production to meet increasing energy demand and to reduce the CO2concentration from atmosphere to reduce global worming.This study is an effort to increase oil production by CO2-EOR from an oil reservoir in Surma basin and to evaluate the oil reservoir as a candidate of CO2 sequestration. The oil reservoir rock is Bhuban sandstone and fluid is heavy oil. High salinity water is also present in the oil reservoir. A compositional reservoir simulation model has been developed for this study. Geo-cellular 3D reservoir grid structure has been constructed by block centered geometry. Reservoir rock properties such as porosity, absolute permeability and net to gross ratio have been modeled using rock properties of Bhuban sandstone. Reservoir oil composition has been determined from liquid chromatograph. Thermodynamic properties of pure components in reservoir oil have been included in the compositional reservoir simulation model. The reservoir has been developed by four CO2 injection wells arranged at the periphery of the reservoir and one oil production well kept at the center of the reservoir. The optimum CO2 injection rate is 500 MSCF/D at pressure 3100 psi by a single well and optimum oil production rate is 4900 STB/D. Dhaka Univ. J. Sci. 70(2): 23-28, 2022 (July)